Arterial hypertension as a predictor of morphofunctional changes development in rats` solitary-vagal complex - Danukalo, M. V.; Melnikova, O. V.; Данукало, Максим Вікторович; Мельнікова, Ольга Валеріївна (Journal of Education, Health and Sport, 2019)
The components of the dorsal vagal complex (DVC), respectively, the nucleus of the solitary tract (NST) and the dorsal motor nucleus (DMN) are key structures in BP regulation. And the adequacy of maintaining BP normal level will depend on functional state of these structures. Indirectly, without applying direct electrophysiological methods it is possible to measure the neurons morpho-functional state analyzing the nucleus size and nucleus acid (NA) concentrationin it. Therefore, the aim of our work was to establish the features of morpho-densitometric indices in the nuclei of the NST and DMN neurons in AH of various origins in experimental animals and to give a comparative analysis of these data. Materials and methods: the study was carried out on 30 mature male rats: 10 control Wistar rats, 10 Wistar rats with modeled endocrine-salt AH (ESAH) and 10 spontaneously hypertensive rats (SHR) with genetically determined hypertension, that most closely corresponds to human essential arterial hypertension (EAH). The histochemical method of staining with gallocyanine-chrome alum by Einarson was used for the evaluation of morphodensitometric characteristics of the DMN and NTS neurons` nuclei: the nucleus area, the content and concentration of nucleic acids in the nucleus Conclusions: Based on the results of our study, the following conclusions can be made: 1. In arterial hypertension, regardless of its pathogenesis, morpho-structural changes occur in the NTS and DMN main afferent and efferent centers of the parasympathetic nervous system. 2. In rats with EAH, the most pronounced changes in the studied indices of neurons` nuclei were observed in DMN. Thus only the neurons` nuclei area significantly changed in the NTS. The distribution of neurons` nuclei by their area in DMN and NTS in SHR rats showed a shift in the curve towards a decrease. 3. In rats with an endocrine-salt model of hypertension, a significant decrease in all morpho-densitometric characteristics of the neurons` nuclei is characteristic in the DMN. The distribution of neurons` nuclei by their area showed a shift of the curve in the direction of decrease compared to the control. In the nuclei of NST neurons, only the content and concentration of NA were reliably low in comparison with control animals. The distribution curve of neurons by the area of heir nuclei in ESAH rats is characterized by a wider size variability than in the control group.
Keywords: nucleus of the solitary tract; dorsal motor nucleus; arterial hypertension; rats